Pengaruh pertumbuhan ekonomi terhadap tingkat kemiskinan dengan pengangguran sebagai mediasi di Probolinggo - Najib Putri, Rosidatul Halim; Yuliana, Indah (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
The problem of poverty is experienced by various countries in the world, both developed countries and developing countries. Poverty is defined as a problem where people are unable to fulfill their needs. Indonesia is a country that has been experiencing poverty problems for a long time. The problem of poverty is influenced by various factors, such as people's income, unemployment, education, location, geography, gender, and environmental location. The purpose of this study was to measure the effect of economic growth on the level of poverty using the unemployment rate as a mediator in the city and district of Probolinggo. This study uses secondary data from BPS Kota and Probolinggo Regency with the variables of poverty, economic growth, and unemployment in 2014–2021 using the Sobel Test method, which utilizes SPSS version 16. The results of this study indicate that economic growth has no significant effect on the poverty rate. The unemployment rate has no significant effect on the poverty rate. And based on Sobel's analysis, it is known that the unemployment rate does not mediate the effect of economic growth on the poverty rate.